2018
DOI: 10.1159/000489287
|View full text |Cite
|
Sign up to set email alerts
|

The Trouble with CBD Oil

Abstract: In just a few years, cannabidiol (CBD) has become immensely popular around the world. After initially being discovered as an effective self-medication for Dravet syndrome in children, CBD is now sold and used to treat a wide range of medical conditions and lifestyle diseases. The cannabinoid CBD, a non-psychoactive isomer of the more infamous tetrahydrocannabinol (THC), is available in a growing number of administration modes, but the most commonly known is CBD oil. There are currently dozens, if not hundreds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
137
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(146 citation statements)
references
References 28 publications
5
137
1
3
Order By: Relevance
“…Hemp‐derived CBD is commercially available and is currently used as a health and food supplement commonly for anxiety and pain relief. This market represents a flourishing industry expected to rise financially and globally . However, the blurred lines between CBD as a licensed medicine and CBD as an over‐the‐counter remedy contribute to the overall lack of understanding of what dose of CBD may be considered therapeutic .…”
Section: Introductionmentioning
confidence: 99%
“…Hemp‐derived CBD is commercially available and is currently used as a health and food supplement commonly for anxiety and pain relief. This market represents a flourishing industry expected to rise financially and globally . However, the blurred lines between CBD as a licensed medicine and CBD as an over‐the‐counter remedy contribute to the overall lack of understanding of what dose of CBD may be considered therapeutic .…”
Section: Introductionmentioning
confidence: 99%
“…A number of public health concerns arise in territories where legislators permit consumption of CME which have not been subject to standard quality assurance requirements that are typically associated with drug marketing authorisation [15, 91]. Reports of inaccurate labelling and batch-to-batch variation of active ingredients within magistral CME preparations confirm fears that these products lack standardisation [29, 91, 92].…”
Section: Resultsmentioning
confidence: 99%
“…Reports of inaccurate labelling and batch-to-batch variation of active ingredients within magistral CME preparations confirm fears that these products lack standardisation [29, 91, 92]. Being able to characterise accurately the complexity of botanical drug forms and to discriminate the efficacy of their constituents both singularly and in combination remains challenging [93].…”
Section: Resultsmentioning
confidence: 99%
“…While the CBD products available to buy either from shops or via the Internet are considered legal, they are not subject to any established testing regimen or quality standards, which may have safety implications. Many products undergo some form of analysis to determine their phytocannabinoid content, although there are currently no accepted guidelines or certification processes to ensure the consistency of such analyses (Hazekamp ). As a result, it is not possible for consumers to be certain that the levels of phytocannabinoids which a product is advertised as containing are indeed accurate, including those which are legally restricted [namely THC and tetrahydrocannabivarin (THCV)].…”
Section: Is Cbd Safe?mentioning
confidence: 99%
“…In addition to the potential for inaccurate labelling of the phytocannabinoid content, CBD‐containing products may be adulterated or contaminated with pesticides or heavy metals (Hazekamp ). A recent analysis conducted by the International Cannabis and Cannabinoid Institute (Prague, Czech Republic) found that out of 29 CBD oil products available on the EU market, 69% of those tested had levels of polycyclic aromatic hydrocarbons above the permissible maximum levels set by the EU (ICCI ).…”
Section: Is Cbd Safe?mentioning
confidence: 99%